Cocaine nephropathy: A rare cause of abnormal nephrograms - Hannah Lamberg, BS; Richard H. Cohan, MD; John D. Millet, MD, MHS (Radiology Case Reports, 2021)
Cocaine use is associated with a variety of renal injuries. Although rhabdomyolysis is the most common cause of cocaine-induced nephropathy, cocaine can also cause renal vasculitis, acute interstitial nephritis, acute tubular necrosis, thrombotic microangiopathy, and renal infarction. We present a rare case of cocaine-induced nephropathy in a 30-year-old male who presented with acute kidney injury and abnormal nephrograms at contrast-enhanced computed tomography. Mechanisms of cocaine-induced renal injury and differential causes of abnormal nephrograms encountered at imaging are discussed. Cocaine-induced nephropathy is a rare but important cause of abnormal nephrograms and should be considered in the differential diagnosis when clinically appropriate.